The unification of the criminal procedure and its impact on the criminal procedure policy of Russia. - I. A. , KUCHERKOV (The journal of contemporary issues in business and government, 2021)
The scientific article discusses the model of unification of criminal procedure based on the interaction of national legal systems. It is justified that the key modern models of the criminal procedure at present are the German, French and English models, which set standards for unification for other states, including for Russia. The article justifies the concept that the criminal procedure policy of Russia, starting in 1864, is based on the unification of the procedural institutions of other legal systems. The Russian Empire unified the criminal procedure with the French model, the Soviet Union introduced German criminal procedural institutions, the criminal procedure of the modern Russian Federation, is the object of competition between the German, French and English models of criminal procedure, which is reflected in the legislative regulation of various institutions of criminal procedure (jury trial, simplified judicial procedures, alternatives to criminal prosecution, appeal of court decisions).